Complete ¹H- and 13C- Resonance Assignment of Methyl 2alpha, 3beta, 24-Tri-O-acetylurs-12-en-28-oate and Methyl 2alpha, 3beta, 24-Tri-O-acetylolean-12-en-28-oate by NMR Spectroscopy - Monte,F.J.Q. (1998)
The complete ¹H and 13C chemical shift assignments of extended hydrogen spin systems in triterpenoid derivatives (methyl 2alpha, 3beta, 24-tri-O-acetylurs-12-en-28-oate and methyl 2alpha, 3beta, 24-tri-O-acetylolean-12-en-28-oate) was accomplished making use of one and two dimensional NMR techniques (HMBC, HMQC, COSY and NOESY).